Highly efficient Tsuji–Trost allylation in water catalyzed by Pd-nanoparticles. Issue 37 (25th April 2017) - Llevot, A.; Monney, B.; Sehlinger, A.; Behrens, S.; Meier, M. A. R.
Abstract : Palladium nanoparticles stabilized by poly(vinylpyrrolidone) catalyze Tsuji–Trost allylations in water with very high turnover numbers. Abstract : Palladium nanoparticles stabilized by poly(vinylpyrrolidone) catalyze Tsuji–Trost allylations in water with very high turnover numbers. The di-allylation of methylene active compounds and the allylation of bio-based phenols was performed in high yield. The allylation of lignin showed a high selectivity towards the phenolic OH groups.